A comparison of capsaicin and menthol as trigeminal modulators of salivary composition for use in oral care applications - Truong, Pham-Quynh-Huong (2023)
Part A: The human oral cavity contains 700 types of bacteria. Gram-negative anaerobe bacteria are associated biofilm formation and oral malodour due to their abundance and metabolism producing volatile sulfur compounds. Human saliva contains Mucin, Proline-Rich Proteins (PRPs), Alpha-Amylase (α-Amylase), Cystatins, Histatins, and Statherin, which contribute to lubricate mouth, protect mucosal integrity and against microorganisms, and digest food. Due to their ability to stimulate the saliva and also have antibacterial activities. In this review, we investigate how menthol and capsaicin affect the salivary flow, oral protein composition, and also their effect on these oral bacteria. Following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, we conducted a literature search using Google Scholar from 1980 to 2023 in English form. The search query was based on the question "How do trigeminal modulators including capsaicin and menthol affect salivary flow, salivary protein composition, and oral microbiomes?" A total of twenty-seven articles were selected for analysis. The results showed that capsaicin still increased the saliva flow at 1 ppm, 5 ppm, 0.005M, 3x10-5M, and 0.3nM concentrations after the first minute of stimulation and then decreased after two minutes. In contrast, menthol did not change the saliva flow at 0.05M and 250 ppm doses and slightly changed the flow at 500 ppm only during the first minute. Regarding protein composition and its changes, MUC5B (above 188kDa), MUC7 (~150kDa), α-Amylase (50-60kDa), PRPs (40-50kDa), Cystatin (~14kDa), Statherin (~6kDa) were identified on 12% SDS-PAGE. Menthol did not increase protein content at 250 ppm and 0.05M whereas 500 ppm menthol increased slightly protein content and significantly increased cystatin S (P < 0.05). Capsaicin slightly increased protein content and significantly increased protein compositions, except MUC5B at 1 ppm and 0.05M. Regarding antibacterial activity measured by MBC and MIC methods, menthol decreased the growth of Bacteroides, P. gingivalis, and F. nucleatum, while capsaicin also decreased the abundance of Bacteroides, P. gingivalis and increased Bacteroides. In conclusion, based on their characteristics, menthol and capsaicin at some concentrations are potential ingredients for oral care applications.